Pathobiology of Helicobacter pylori Infection in Children - Robert H Riddell (Canadian Journal of Gastroenterology)
In the paediatric population, the associations of Helicobacter pylori with gastritis, gastric ulcer, duodenitis and duodenal ulcer, and with duodenal gastric surface metaplasia and disorders of the D cell-G cell axis resulting in hypergastrinemia, are well established and in many ways resemble their counterparts in adults. Eradication of H pylori invariably results in the reversal of these diseases with time. There are also suggestions that gastric surface metaplasia is more extensive in children with H pylori, and may be the site of duodenal H pylori infection and associated duodenal erosions or ulcers. There is no consensus as to whether H pylori in children is more or less severe than in adults. In one paediatric cohort, H pylori was associated with increased intensity of inflammation, while other studies suggest that acute inflammation may be less intense in children overall but that chronic inflammation may be increased in intensity, including lymphoid hyperplasia, which in turn may correlate with endoscopic nodularity. Lymphoid hyperplasia and nodular gastritis appear to be more frequent in children than in adults and usually regress following H pylori eradication. However, in children, other diseases or morphological abnormalities, including some loss of glands (atrophy), occasionally intestinal metaplasia, lymphoproliferative diseases including low grade mucosal-associated lymphoid tissue lymphoma, lymphocytic gastritis and hypertrophic gastritis/Menetrier’s disease, are much less frequently associated with H pylori than in adults. Other associations are rarely seen in children, primarily because the time required for these to develop takes the individual to adulthood; for example, while intestinal metaplasia occurs in the pediatric population, the complications of adenoma/dysplasia and carcinoma are rare. In adults, inflammatory and hyperplastic polyps, atrophic gastritis and pernicious anemia, and in some patients granulomas (granulomatous gastritis), may also be associated with H pylori infection. Greater awareness of the spectrum of diseases associated with H pylori may well lead to their increased recognition in the paediatric population. Some diseases, particularly Crohn’s disease, but also human immunodeficiency virus infection, have a negative association with H pylori that appears not to be simply a result of the excess antibiotic therapy that these patients receive. These variations in association and reactions to H pylori, some of which are age-related, may allow the different host responses to H pylori that occur in humans to be examined.